Awareness of obesity and the desire to change among adults in Abu Dhabi – United Arab Emirates 2024 - Mohamed, Israa M. (International Journal of Research in Medical Sciences, 2025)
Background: Obesity is a growing epidemic worldwide. In recent years, obesity rates have risen rapidly, likely due to the widespread availability of online services and technologies that, while enhancing our lives, reduce physical activity. Although obesity is a preventable disease, prevention relies heavily on health education and the motivation to adopt lifestyle changes. This study aims to assess awareness of obesity and the desire to change among adults in Abu Dhabi, as of September 2024. Methods: The minimum sample size was calculated considering a level of confidence 95%, expected prevalence of 50% and precision of 0.05, final sample size was 255 participants. Data was collected through an online questionnaire using Google forms. Data analysis was conducted using Microsoft Excel and the results were presented in graphs and tables. Results: In this study, 255 adults participated. Around 40.8% reported being on a diet, with the most commonly followed diet being a low carbohydrate diet (51.9%), Participants were aware of the importance of exercise, with most exercising 1-2 times per week. Only a small proportion have undergone medical procedure. The majority had a normal body mass index (18.6-24.9). About 84.7% of participants attempted to lose weight, primarily inspired by personal decision. Overall, participants showed good knowledge and a strong motivation to manage their weight. Conclusions: The study showed that awareness of obesity in the Abu Dhabi community has increased and individuals are taking steps to manage their weight. Therefore, health education can make a significant impact on promoting healthier lifestyles among adults.